2022
DOI: 10.4028/p-vthp40
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared LEDs-Based Non-Invasive Blood Sugar Testing for Detecting Blood Sugar Levels on Diabetic Care

Abstract: Diabetes Mellitus, with its rapid development and various complications that have caused it, has become one of the deadliest diseases in the world. Early detection efforts to raise blood sugar levels can help to avoid a variety of complications. Measuring devices are needed to find out blood sugar levels detect how much sugar is in the blood. The blood sugar measuring device is invasive by taking blood from capillaries tested both in the lab and using portable testing instruments. The use of this tool results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The experimental results showed that the portable and light NIR spectrometer can be easily used (Yu et al, 2021a). A NIR-LEDs-Based detection system was also proposed by Badriah et al to measure blood sugar levels on diabetic care (Badriah et al, 2022). Belay et al (2020) presented a three-segment grating spectrometer, aimed to help in cancer diagnosis.…”
Section: Applications In Medical Diagnosticmentioning
confidence: 99%
“…The experimental results showed that the portable and light NIR spectrometer can be easily used (Yu et al, 2021a). A NIR-LEDs-Based detection system was also proposed by Badriah et al to measure blood sugar levels on diabetic care (Badriah et al, 2022). Belay et al (2020) presented a three-segment grating spectrometer, aimed to help in cancer diagnosis.…”
Section: Applications In Medical Diagnosticmentioning
confidence: 99%